Analisis Kualitas Pelayanan Online Pendaftaran Administrasi Kependudukan (Poedak) di Dinas Kependudukan dan Pencatatan Sipil Kabupaten Gresik - Haniifah Rihadatulsyani; Rachmawati Novaria; Adi Soesiantoro (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
The study was intended to anlyze evaluations regarding the quality related to online registration of population administration at the Population and Civil Registration of Gresik Regency. The method used in the study is descriptive research with a qualitative approach. This descriptive research method was chosen to present data systematically, factually, and accurately regarding the facts in the field. This research model uses an approach to the implementation of service quality at the Population and Civil Registration Service of Gresik Regency. The results of this study are statutory regulations (Law Of The Republic Of Indonesia Number 25 Of 2009) where publics services is a primary obligation of all government officials to organize activities or a series of activities in order to fulfill service needs in accordance with statutory regulations for every citizen and resident for goods and services provided by public service providers. And from this study we can see together that the supporting factors of the analysis of the quality of online registration service of Gresik Regency.